2005
DOI: 10.4049/jimmunol.174.3.1213
|View full text |Cite
|
Sign up to set email alerts
|

Roles for Common Cytokine Receptor γ-Chain-Dependent Cytokines in the Generation, Differentiation, and Maturation of NK Cell Precursors and Peripheral NK Cells in Vivo

Abstract: NK cells differentiate in adult mice from bone marrow hemopoietic progenitors. Cytokines, including those that signal via receptors using the common cytokine receptor γ-chain (γc), have been implicated at various stages of NK cell development. We have previously described committed NK cell precursors (NKPs), which have the capacity to generate NK cells, but not B, T, erythroid, or myeloid cells, after in vitro culture or transfer to a fetal thymic microenvironment. NKPs express the CD122 Ag (β chain of the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
238
4
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 249 publications
(258 citation statements)
references
References 46 publications
15
238
4
1
Order By: Relevance
“…In addition, we examined the expression of CD43 (sialoadhesin) and CD11b (integrin aM), which serve as markers of functional NK cell maturation [8,33]. However, T and/or B cell deficiency had no significant effect on the acquisition of CD43 and CD11b by BM or spleen NK cells (data not shown).…”
Section: Markers Of Activation or Maturation On Nk Cells In Lymphopenmentioning
confidence: 99%
“…In addition, we examined the expression of CD43 (sialoadhesin) and CD11b (integrin aM), which serve as markers of functional NK cell maturation [8,33]. However, T and/or B cell deficiency had no significant effect on the acquisition of CD43 and CD11b by BM or spleen NK cells (data not shown).…”
Section: Markers Of Activation or Maturation On Nk Cells In Lymphopenmentioning
confidence: 99%
“…During lymphoid development, distinct cytokines have been identified that promote the survival and proliferation of B, T and NK cell precursors in the bone marrow and in the thymus. For example, IL-7 and stem cell factor are crucial for early thymocyte differentiation, IL-7 and fetal liver kinase-2 ligand drive B cell development, and IL-15 is essential for the generation of immature NK cells [1][2][3][4][5]. These observations indicate that cytokines have specific (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…CD3 À CD122 þ immature NKPs are the earliest known progenitors committed to become NK cells, defined by the absence of mature markers such as NK1.1, NKG2D, NKG2A/C/E, Ly49, CD49b and CD11b. 31,33 Our results show that the lack of p85a resulted in the reduction of CD3 À CD122 þ NK1.1 À CD49b À progenitors in the BM and spleen. Similar reductions were also observed in (Figures 2c and d).…”
Section: Resultsmentioning
confidence: 63%
“…49 Also, expression of CD122 by early progenitors uniquely marks the committed NKPs. 33 Both the initiation of CD122 expression and its level in p85a À/À NK cells were not affected, indicating that p85a is dispensable for this developmental step. Also, percentages of CD3 À CD122 þ cells were not altered in p85a À/À mice.…”
Section: Discussionmentioning
confidence: 95%